Improvement of Marwari sheep in hot arid climate - DASS, GOPAL; SINGH, V K (The Indian Journal of Animal Sciences, 2014)
The Marwari breed is being improved through selection. The least-square means of body weights of lambs at birth, 3,6, 9 and 12 months of age were 3.15±0.01, 14.01±0.06, 19.37±0.07, 23.08±0.07 and 2S.75±0.08 kg respectively. The elite lambs gained comparatively more weights, than tester lambs. The overall least-squares means of wool production were 849.37±05.58, 487.82±03.51, 1335.57±07.94g. The elite animals were superior to the tester groups for all the clips.The fibre diameters were 36.15±0.27 with 32. 77±0.61 % hetro, 18.34±0.42% hairy and 51.22±0. 73% medulation. The overall lambing percentage on the ewes available bases were 85.0,88.1 and 68.5% in tester group during 1997, 1998 and 1999 respectively. These figures were 83.6, 80.1 and 72.9% for elite group. The overall survivability was 97.7, 99.2 and 98.8%, respectively, for 1996-97, 1997-98 and 1998-99. Results of elite rams indicated that rams selected through 2-stage selection of male lambs using 6 monthly body weight and first 6 monthly greasy fleece yield, brought the improvement in growth, wool production and quality, reproduction and survivability of Marwari sheep. The wool quality parameters indicated that the wool is ofa good carpet quality with average diameter around 36u. However, the average medulation of 50% is still on higher side. As far as woof quality for carpet production is concerned there is need to reduce magnitude of hairy fibres through appropriate breeding programme.